Reversible Self-Dual Codes over Finite Field - Hidayat, Ardi Nur; Krisnawati, Vira Hari; Alghofari, Abdul Rouf (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
Reversible self-dual code is a linear code which combine the properties from self-dual code and reversible code. Previous research shows that reversible self-dual codes have only been developed over field of order 2 and order 4. In this article, we construct reversible self-dual code over any finite field of order F_q ,  with natural number q=2.  We first examine and prove some of fundamental properties of reversible self-dual code over . After a thorough analysis these, we obtain a new generator matrix of reversible self-dual code.  A new generator matrix is derived from existing self-dual and reversible self-dual code over . It will be shown that a new reversible self-dual over  can be constructs from one and more existing code by specific algebraic methods. Furthermore, using this construction, we determine the minimum distance of reversible self-dual code and ensuring its optimal performance in various applications.